Inositol 1,4,5-trisphosphate receptors in endocrine cells: localization and association in hetero- and homotetramers. - Nucifora, F C (1996)
The inositol 1,4,5-trisphosphate receptor (IP3R) is an intracellular calcium channel involved in coupling cell membrane receptors to calcium signal transduction pathways within cells including endocrine cells. Several isoforms (I, II, and III) of IP3Rs have been identified, which are encoded by separate genes, and are expressed in many tissues with differing patterns of cellular expression. We have generated specific affinity-purified polyclonal anti-peptide antibodies to each of the three isoforms. Western blot analysis of RINm5F and ATt20 cells shows high levels of endogenously expressed type I and type III IP3R, but undetectable levels of type II. Immunofluorescence studies revealed an endoplasmic reticulum-like pattern similar to BiP, an ER marker. In contrast with previous claims, both type I and type III IP3Rs were absent from the secretory granules of ATt20 cells. Western blots of sucrose gradients and gel filtration probed with antibodies to either type I or type III showed a molecular weight of greater than 1,000 kDa consistent with a tetrameric structure. Co-immunoprecipitation experiments indicated that most of the receptors were present as heterotetramers. Homotetramers were identified for the type III IP3R; however, type I homotetramers were undetectable. These data suggest that molecular association of IP3Rs into heterotetrameric forms can contribute to the complexity of the regulation of Ca2+ release from ER by IP3Rs within cells.